Efforts to improve music education in Turkey - Mustafa, Kabatas (Academic Journals, 2017)
It is seen how state policies are effective in education when it is thought that education is organized according to the principle of making the individual useful for the community. Given that education policies should be effective in all areas of education, music education is expected to be present in a common political attitude in the fields of general, ethical and professional music education (Kucukahmet, 2000) . It can be said that the most obvious change in the music education policies came with the Republican era in Turkey. These innovations was not enough only in state administration and social life. Ataturk, also wanted to reach a level of contemporary civilization in cultural matters. Taking Turkish music to the international level by taking advantage of the music, knowledge and techniques of the West constitutes the aim of Ataturk's work on music. National fine sentiments, high sayings about thought, gathering of sayings; We need to handle them the day before according to the final musical bases. In this way, Turkish national music can rise, it can take place in international music” he said. And development politics have been prepared in the field of music as well. Accordingly, there is a need for a music education development policy with continuity and sustainability in the context of today's music education. In this direction; Evaluating the reflections of educational development policies in the Republican period on music education and developing suggestions constitute the main problem of this research. This research: consideration of the developmental policies of music education applied in the Republican period with an inductionist approach is important from the point of view of the general view of music education policies of the Republican period, and as a source for researchers and field experts. In this research, it tried to describe the situation regarding the music education policies of the Republican period. Research is a descriptive screening model suitable for qualitative research approach. Key words: Education, music, music education, culture, music culture.
Keywords: 9. Industry and infrastructure; 4. Education; 11. Sustainability; 8. Economic growth; 10. No inequality; 16. Peace & justice; 12. Responsible consumption